Photodetectors based on carbon nanotubes deposited by using a spray technique on semi-insulating gallium arsenide - Melisi, Domenico; Nitti, Maria Angela; Valentini, Marco; Valentini, Antonio; Ligonzo, Teresa; De Pascali, Giuseppe; Ambrico, Marianna (Beilstein Journal of Nanotechnology, 2014)
In this paper, a spray technique is used to perform low temperature deposition of multi-wall carbon nanotubes on semi-insulating gallium arsenide in order to obtain photodectors. A dispersion of nanotube powder in non-polar 1,2-dichloroethane is used as starting material. The morphological properties of the deposited films has been analysed by means of electron microscopy, in scanning and transmission mode. Detectors with different layouts have been prepared and current–voltage characteristics have been recorded in the dark and under irradiation with light in the range from ultraviolet to near infrared. The device spectral efficiency obtained from the electrical characterization is finally reported and an improvement of the photodetector behavior due to the nanotubes is presented and discussed.
Keywords: multi-wall carbon nanotubes; photodetectors; spray technique; UV–NIR

(untitled) - Smith, F. W.; Le, H. Q.; Diadiuk, V.; Hollis, M. A.; Calawa, A. R.; Gupta, S.; Frankel, M.; Dykaar, D. R.; Mourou, G. A.; Hsiang, T. Y. (Appl. Phys. Lett., 1989)

(untitled) - Moglestue, C.; Rosenzweig, J.; Kuhl, J.; Klingenstein, M.; Lambsdorff, M.; Axmann, A.; Schneider, J.; Hülsmann, A. J. (J. Appl. Phys., 1991)

High frequency characterization of carbon nanotube for device application - Decrossas, E. (University of Arkansas, 2012)

(untitled) - Tans, S. J.; Verschueren, A. R. M.; Dekker, C. (Nature, 1998)

(untitled) - Kamat, P. V. (Nano Today, 2006)

(untitled) - Moon, J. S.; Park, J. H.; Lee, T. Y.; Kim, Y. W.; Yoo, J. B.; Park, C. Y.; Kim, J. M.; Jin, K. W. (Diamond Relat. Mater., 2005)

(untitled) - Melisi, D.; Nitti, M. A.; Valentini, M.; Valentini, A.; Ditaranto, N.; Cioffi, N.; Di Franco, C. (Thin Solid Films, 2013)

(untitled) - Ruffini, G.; Dunne, S.; Farrés, E.; Pallares, J. M.; Ray, C.; Mendoza, E.; Silva, R.; Grau, C. (Sens. Actuators, A, 2006)

(untitled) - Artru, X.; Fomin, S. P.; Shul’ga, N. F.; Ispirian, K. A.; Zhevago, N. K. (Phys. Rep., 2005)

(untitled) - Ren, Z. F.; Huang, Z. P.; Xu, J. W.; Wang, J. H.; Bush, P.; Siegal, M. P.; Provencio, P. N. (Science, 1998)

(untitled) - Che, G.; Lakshimi, B. B.; Martin, C. R.; Fisher, R. (Chem. Mater., 1998)

(untitled) - Kumar, M.; Ando, Y. (J. Nanosci. Nanotechnol., 2010)

(untitled) - Ambrosio, A.; Aramo, C.; Battiston, R.; Castrucci, P.; Cilmo, M.; De Crescenzi, M.; Fiandrini, E.; Grossi, V.; Guarino, F.; Maddalena, P.; Nappi, E.; Passacantando, M.; et al. (J. Instrum., 2012)

(untitled) - Ambrosio, A.; Ambrosio, M.; Ambrosone, G.; Carillo, V.; Coscia, U.; Grossi, V.; Maddalena, P.; Passacantando, M.; Perillo, E.; Raulo, A.; Samtucci, S. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2008)

(untitled) - Aramo, C.; Ambrosio, A.; Ambrosio, M.; Castrucci, P.; Cilmo, M.; De Crescenzi, M.; Fiandrini, E.; Guarino, F.; Grossi, V.; Nappi, E.; Passacantando, M.; Pignatel, G.; et al. (Nucl. Instrum. Methods Phys. Res., Sect. A, 2012)

(untitled) - Cola, A.; Lupo, G.; Vasanelli, L.; Valentini, A. (J. Appl. Phys., 1992)

(untitled) - Mridha, S.; Basak, D. (J. Appl. Phys., 2007)

Semiconductors: data handbook - Madelung, O. (Springer, 2004)

Photoconductivity of solids - Bube, R. H. (John Wiley & Sons, Inc, 1960)

Physics of semiconductor devices - Sze, S. M.; Kwok, K. N. (John Wiley & Sons, 2007)